CEGAH STUNTING MELALUI EDUKASI ASUPAN ZAT BESI PADA IBU HAMIL YANG BERISIKO ANEMIA DAN KEKURANGAN ENERGI KRONIS - Nurhannifah Rizky Tampubolon; Dita Erwinda; Fira Amalia Hanifah; Meliza Ningsih; Kenisa Nazlia Rizal; Ihan Crisna Dwi Eryo (Stikes Yarsi Mataram, 2023)
Anemia is a condition of the body where hemoglobin (Hb) levels in the blood are lower than normal. Anemia in pregnant women can occur due to a diet that is less diverse and unbalanced nutrition, lack of intake of foods containing iron, repeated pregnancies in a short time, pregnant women who experience chronic energy deficiency (SEZ) and iron loss when pregnant women experience infection. SEZ in pregnant women indicates that there has been malnutrition for a long period of time, which can last for several months or years. The purpose of this iron intake education activity is to increase the knowledge of pregnant women about the problems of stunting, anemia, and (SEZ) so that the risk factors for stunting can be minimized. Education is given to the target group with a personal approach, namely visiting directly to their homes, and the material is delivered using an interactive lecture method with leaflet media. The results obtained were an increase in knowledge by 48% related to the problem of anemia and chronic energy deficiency (SEZ).